Guide to Security and Data Integrity: Protect Your Network From Hackers, System Failures, and Natural Disasters - Farley, Marc; Stearns Tom; Hsu Jeffrey (Berkeley McGraw-Hill, 1996)
Guide to Security and Data Integrity: Protect Your Network From Hackers, System Failures, and Natural Disasters. This book was written to help LAN administrators understand the issues and technology of data protection in this changing world. The concept was to use a multidisciplinary approach to give the reader a broad prspective. Therefore, a wide range of topics are presented, including backup and recovery, arhiving, hierarchical storage management (HSM), redundant systems, system security, user security management and policies, authentication, encryption, viruses, and disaster recovery planning.
Keywords: Science